2020
DOI: 10.4103/jfcm.jfcm_173_20
|View full text |Cite
|
Sign up to set email alerts
|

Mean glycosylated hemoglobin in children with type 1 diabetes at King Fahad Medical City, Riyadh, Saudi Arabia

Abstract: BACKGROUND: Type 1 diabetes is the third most common chronic disease among teenagers. In Saudi Arabia, there is a gap of knowledge regarding hemoglobin A1C (HbA1c) concentration levels, and adherence to regular follow-up visits by patients. The aim of this study was to determine the mean glycosylated hemoglobin (HbA1c) levels in diabetic children who have been diagnosed with type 1 diabetes and were being followed up at a tertiary care center in Saudi Arabia. MATERIALS AND METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…We found that the mean HbA1c in our study population was 10.70%, which appears to be moderate high level compared to the values of HbA1c recommended for 10.6% in the result of (Alsaheel et al, 2020) at Saudi Arabia previous study [18]. It is also to be to higher compared than values reported in previous studies; the mean HbA1c was 7.8% in Germany and Austria, 7.6% (± SD 1.5) for Polish children and adolescents with long-term type 1 diabetes, and >9.3% in more than half (53%) of the patients in a study conducted in Sweden [19][20][21].…”
Section: Discussioncontrasting
confidence: 57%
“…We found that the mean HbA1c in our study population was 10.70%, which appears to be moderate high level compared to the values of HbA1c recommended for 10.6% in the result of (Alsaheel et al, 2020) at Saudi Arabia previous study [18]. It is also to be to higher compared than values reported in previous studies; the mean HbA1c was 7.8% in Germany and Austria, 7.6% (± SD 1.5) for Polish children and adolescents with long-term type 1 diabetes, and >9.3% in more than half (53%) of the patients in a study conducted in Sweden [19][20][21].…”
Section: Discussioncontrasting
confidence: 57%
“…The duration of diabetes also affects glycaemic control. As the age and duration of the disease increase, the glycaemic control worsens, as shown by the recent study [ 10 , 11 ]. The honeymoon phase and supervised parental care in the early years of diagnosis are factors associated with better glycaemic control in the early years after diagnosis.…”
Section: Discussionmentioning
confidence: 94%
“…Various factors influence diabetic control including age, gender, duration of disease, rural status, access to insurance and health care, and associated autoimmune diseases. However, the data on predictors affecting glycaemic control are scarce and variable [ 5 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%